2016
DOI: 10.1002/cjce.22545
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CO2 separation from synthesis CO2/CH4 mixture utilizing tetra‐n‐butyl ammonium bromide semi‐hydrate

Abstract: Semi‐clathrate hydrates of tetra‐n‐butyl ammonium bromide (TBAB) offer a potential solution for separation of CO2 from biogas. In this work, gas hydrate formation from a CO2/CH4 mixture in distilled water with 0.05 g/g (5 wt%) TBAB was examined at 275, 277, and 279 K with pressures of 4000, 5000, and 6000 kPa. The compositional changes of the gas phase were analyzed continuously during the hydrate formation process. The results indicated that no significant induction occurred during hydrate formation. The CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The CH 4 recovery ratio decreased as the initial gas/liquid volume ratio decreased. Fan 25 and Zang 56 et al have also reported similar phenomena when using TBAB as an additive for hydrate-based CO 2 /CH 4 separation. The low initial gas/liquid volume ratio indicated that the hydrate-forming solution was excessive, and vice versa.…”
Section: Resultsmentioning
confidence: 69%
“…The CH 4 recovery ratio decreased as the initial gas/liquid volume ratio decreased. Fan 25 and Zang 56 et al have also reported similar phenomena when using TBAB as an additive for hydrate-based CO 2 /CH 4 separation. The low initial gas/liquid volume ratio indicated that the hydrate-forming solution was excessive, and vice versa.…”
Section: Resultsmentioning
confidence: 69%
“…By considering the total amount of gas in the mixture gas consumed under different operating conditions, it was found that the best CO 2 separation and CH 4 recovery results were obtained with the largest CO 2 and CH 4 consumption proportions, respectively. Meanwhile, the gas consumption decreased significantly compared with that of binary gas mixture (CH 4 /CO 2 = 50/50) under same experiment conditions . The presence of N 2 increased the phase equilibrium pressures of the mixed gas hydrate under same temperatures, reduced the reaction driving force.…”
Section: Resultsmentioning
confidence: 88%
“…Therefore, the hydrate reaction process within 2 h and the kinetic characteristics of the resulting hydrate formation were studied in this work. Additionally, the amount of gas consumed in 2 h ( N 2h ) was calculated and compared to that consumed for the completed hydrate reaction ( N total ), using a previously reported method . The time required for the hydrate reaction to completely finish was defined as the time when the pressure decrease per minute was less than 0.01 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…The best result is experiment 4, under the condition of 2 MPa, subcooling of 6 K, and 5 wt % TBAB, and the separation factor is 37.05. Figure 15 shows the CO 2 separation factor in different reports, 41,69,70 and it is obvious from Figure 15 that the CO 2 separation factor obtained by the constant pressure operation at low pressure is significantly higher than that obtained by the nonconstant pressure operation at high pressure. Therefore, it is suggested that CO 2 capture from the lean-CH 4 /CO 2 mixture should be carried out in a 5 wt % Energy & Fuels…”
Section: Effects Of Tbab Concentration On Hbgs Undermentioning
confidence: 96%